APOE genotype influences the gut microbiome structure and function in humans and mice: relevance for Alzheimer's disease pathophysiology. Issue 7 (8th April 2019) - Tran, Tam T. T.; Corsini, Simone; Kellingray, Lee; Hegarty, Claire; Le Gall, Gwénaëlle; Narbad, Arjan; Müller, Michael; Tejera, Noemi; O'Toole, Paul W.; Minihane, Anne-Marie; Vauzour, David
ABSTRACT: Apolipoprotein E ( APOE ) genotype is the strongest prevalent genetic risk factor for Alzheimer's disease (AD). Numerous studies have provided insights into the pathologic mechanisms. However, a comprehensive understanding of the impact of APOE genotype on microflora speciation and metabolism is completely lacking. In this study, we investigated the association between APOE genotype and the gut microbiome composition in human and APOE–targeted replacement (TR) transgenic mice. Fecal microbiota amplicon sequencing from matched individuals with different APOE genotypes revealed no significant differences in overall microbiota diversity in group‐aggregated human APOE genotypes. However, several bacterial taxa showed significantly different relative abundance between APOE genotypes. Notably, we detected an association of Prevotellaceae and Ruminococcaceae and several butyrate‐producing genera abundances with APOE genotypes. These findings were confirmed by comparing the gut microbiota of APOE ‐TR mice. Furthermore, metabolomic analysis of murine fecal water detected significant differences in microbe‐associated amino acids and short‐chain fatty acids between APOE genotypes. Together, these findings indicate that APOE genotype is associated with specific gut microbiome profiles in both humans and APOE ‐TR mice. This suggests that the gut microbiome is worth further investigation as a potential target to mitigate the deleterious impact of the APOE4 allele on cognitive decline and the prevention of AD.—Tran, T. T. T., Corsini, S., Kellingray, L., Hegarty, C., Le Gall, G., Narbad, A., Müller, M., Tejera, N., O'Toole, P. W., Minihane, A.‐M., Vauzour, D . APOE genotype influences the gut microbiome structure and function in humans and mice: relevance for Alzheimer's disease pathophysiology. FASEB J. 33, 8221–8231 (2019). www.fasebj.org